OPTIMIZATION OF BIOLOGICAL SHIELD FOR BORON NEUTRON CAPTURE CANCER THERAPY (BNCT) AT KARTINI RESEARCH REACTOR - Gani Priambodo; Fahrudin Nugroho; Dwi Satya Palupi; Rosilatul Zailani; Yohannes Sardjono (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2017)
A study to optimize a model of neutron radiation shielding for BNCT facility in the irradiation room has been performed. The collimator used in this study is a predesigned collimator from earlier studies. The model includes the selection of the materials and the thickness of materials used for radiation shield. The radiation shield is required to absorb leaking radiation in order to protect workers at the threshold dose of 20 mSv/year. The considered materials were barite concrete, paraffin, stainless steel 304 and lead. The leaking neutron radiation dose rates have been determined using Monte Carlo N Particle Version Extended (MCNPX) with a radiation dose limit rate that is less than 10 µSv/hour. This dose limit is in accordance with BAPETEN regulation related the threshold dose for workers, in which the working duration is 8 hours per day and 5 days per week. It is recommended that the best model for the irradiation room has a dimension 30 cm width, 30 cm length, 30 cm height and a main layer of irradiation room shielding made from the material paraffin which is 68 cm thickness on the left side and bottom of the irradiation room, 70 cm thickness on the right side of the iradiation room, 45 cm thickness on the front of the irradiation room and 67 cm thickness on the top of the irradiation room. The additional layers of 15 cm and 10 cm thickness are used along with paraffin in order to reduce the intensity of primary radiation from piercing the beamport after two primary layers. There is no neutron radiation leakage in this model.Keywords: Radiation shielding, BNCT, MCNPX, radiation dose rate, piercing beamport. OPTIMASI PERISAI RADIASI NEUTRON FASILITAS RUANGAN IRADIASI UNTUK BORON NEUTRON CAPTURE CANCER THERAPY (BNCT) DENGAN SUMBER BEAMPORT TEMBUS REAKTOR KARTINI. Telah dilakukan pemodelan perisai radiasi neutron untuk fasilitas Boron Neutron Capture Therapy (BNCT) pada sekeliling ruangan iradiasi. Pemodelan mencakup pemilihan bahan dan tebal yang digunakan untuk perisai radiasi. Perisai diharuskan mampu menahan radiasi yang keluar ruangan sehingga dosis radiasi berada di bawah ambang dosis bagi pekerja radiasi sebesar 20 mSv/tahun. Bahan yang dipertimbangkan adalah beton barit, paraffin, stainless steel 304 dan timbal. Perhitungan laju dosis neutron epitermal dilakukan dengan menggunakan program Monte Carlo N Particle Version Extended (MCNPX) dengan batasan laju dosis radiasi kurang dari 10 µSv/jam, sesuai dengan peraturan Kepala BAPETEN mengenai batas ambang laju dosis pekerja radiasi, dengan asumsi perhitungan waktu kerja 8 jam per hari dan 5 hari per minggu. Desain pertama dari empat desain yang telah dibuat kemudian dipilih sebagai desain yang direkomendasikan dengan laju dosis di bawah batas ambang 10 µSv/jam. Ruangan iradiasi memiliki dimensi panjang 30 cm, lebar 30 cm dan tinggi 30 cm. Lapisan utama perisai pada desain pertama berbahan paraffin setebal 68 cm pada sisi kiri dan bawah ruangan, 70 cm pada sisi kanan ruangan, 45 cm pada sisi depan ruangan dan 67 cm pada sisi atas ruangan. Paraffin setebal 15 cm dan 10 cm ditambahkan sebagai peredam intensitas radiasi primer dari beamport tembus yang masih cukup besar.Kata Kunci: perisai radiasi, BNCT, MCNPX, laju dosis radiasi, beamport tembus.